Compact Rectifier With Wide Range of Output Load Based on Self-Bias Impedance Compensation - Wu, Pengde; Li, Yuxin; Chen, Yi-Dan; Yu, Peng-Yu; Cheng, Yuhua; Liu, Changjun (IEEE transactions on power electronics, 2025)
One of the challenges in rectifiers is that their efficiency is significantly affected by variations in output load and input power. In this brief, we propose a compact rectifier based on dynamic self-bias impedance compensation (SBIC) between two subrectifiers operating in low-load and high-load regions. Their input impedance can dynamically compensate for each other as the output load increases. Consequently, the impact of the nonlinear effect of the diode, caused by the biasing of the dc output voltage, can be reduced. Theoretical analyses were carried out, and corresponding equations were formulated for designing the SBIC. For validation, a prototype was simulated, fabricated, and characterized. At 0-dB·m input power, the rectifier demonstrated a measured efficiency of over 50% with the output load from 0.4 to 9 k Ω , achieving up to 21% improvement in the load range compared to that of a single-diode rectifier. The reflection coefficient remains below −10 dB with an output load between 0.5 and 9 k Ω , and at the same time, good performance can be maintained in the range of input power from −15 to 10 dB·m.